Supporters' experiences of sensory characteristics of children with profound intellectual and multiple disabilities in after‐school daycare centres: A qualitative study - Yuta Koto; Machiko Tomozawa; Toshiaki Sato; Kazuteru Niinomi; Norio Sakai; Toshisaburo Nagai (Wiley, 2023)
Abstract Aim To examine how supporters working at after‐school daycare centres, who are involved in the lives of children with profound intellectual and multiple disabilities in the community, pay attention to the sensory characteristics of these children and provide support. Design A qualitative descriptive design. Methods Data were collected through semi‐structured interviews with 20 supporters in after‐school daycare centres. Interview transcripts were analysed via qualitative content analysis. Results The participants' years of involvement in supporting children with profound intellectual and multiple disabilities ranged from 0.5 to 40 years, with an average of 9.8 years. Data were classified into 68 subcategories, 11 categories and three themes: understanding sensory characteristics and devising support, systematic support and challenges supporting the children. Supporters dealt with physical complications and cooperated with other caregivers to understand and respond to children's sensory characteristics. Difficulties dealing with sensory characteristics, challenges due to the supporters' own characteristics and challenges with the facility's infrastructure were identified. The findings could guide sensory characteristics considerations and support systems in after‐school daycare facilities for children with profound intellectual and multiple disabilities. Both support content and challenges in supporting these children were identified.